Domesticity and Dirt Housewives and Domestic Servants in the United States, 1920-1945 - Palmer, Phyllis (Temple University Press, 1989)
In the era after Suffrage, white middle-class housewives abandoned moves toward paid work for themselves, embraced domestic life, and felt entitled to servants. In Domesticity and Dirt, Phyllis Palmer examines the cultural norms that led such women to take on the ornamental and emotional elements of the job while relegating the hard physical work and demeaning service tasks to servants-mainly women of color. Using novels, films, magazine articles, home economics texts, and government-funded domestic training course manuals, the author details cultural expectations about middle-class homelife. Palmer describes how government-funded education programs encouraged the divisions of labor and identity and undercut domestic workers' organized efforts during the 1930s to win inclusion in New Deal programs regulating labor conditions. Aided by less powerful black civil rights groups, without the assistance of trade unions or women's clubs, domestics failed to win legal protections and the legal authority and self-respect these brought to covered workers. The author also reveals how middle- class women responded ambivalently to the call to aid women workers when labor reforms threatened their domestic arrangements. Throughout her study, Palmer questions why white middle-class women looked to new technology and domestic help to deal with cultural demands upon "the perfect housewife" rather than expecting their husbands to help. When the supply of servants declined during the 1950s, middle-class housewives were left isolated with lots of housework. Although they rapidly followed their servants into paid work outside the home, they remain responsible for housework and child care.